Sweetened beverages in young adults and it's association to adiposity and metabolic risk - Amigo Hugo Cartagena; José Alberto Ortega-Garrido; Patricia Bustos-Muñoz (Instituto Nacional de Salud Pública, 2019)
Objective. To estimate the association between sweetened beverages (SB) consumption with adiposity indicators and metabolic status among young Chilean adults. Materials and methods. We analyzed food frequency consumption, body mass index (BMC), waist circumference (WC), body fat percentage (BFP), glucose and triglycerides in 931 young adults randomly selected from Valparaiso Region using multivariate regression models controlling confusion and interactions factors. Results. The median age was 24.9 years; (95%CI: 92.3-95.3) reported SB consumption, 33.1% received more than two portions (≥500 ml) daily what was associated with an increase in glycemia (β=2.40; p=0.024) (both sexes), with BMI (β=1.48, p=0.04), WC (β= 4.50; p=0.009) and BFP (β=3.02, p< 0.001) only in women. Conclusion. High consumption of SB increases glycemia in young adults and only in women, indicators of adiposity, relevant antecedents to formulate policies that decrease SB consumption and its consequences.